(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Theo perator algebras associated to dynamical/topological/analytic objects, and their classiﬁcation via these objects, have been the subject of study by many authors for almost 50 years, beginning with the work of Arveson [4] and Arveson and Josephson [13]. The main theme of this line of research, as is the main theme of this Paper, is to identify the extent to which the dynamical objects classify their associated non-self operator algebras. We shall mainly focus on classiﬁcation of non-self-adjoint adjoint tensor operator algebras arising from a single C*-correspondence over a commutative C*-algebra, although a profusion of results have been obtained in other contexts to mention only some.